A Theory of Stock Exchange Competition and Innovation: Will the Market Fix the Market? - Eric B. Budish; Robin S. Lee; John J. Shim (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2020)
This paper builds a new model of financial exchange competition, tailored to the institutional details of the modern US stock market. In equilibrium, exchange trading fees are competitive but exchanges are able to earn economic profits from the sale of speed technology. We document stylized facts consistent with these results. We then use the model to analyze incentives for market design innovation. The novel tension between private and social innovation incentives is incumbents' rents from speed technology in the status quo. This creates a disincentive to adopt new market designs that eliminate latency arbitrage and the high-frequency trading arms race.
Keywords: 330; market design; innovation; financial exchanges; industrial organization; platform markets; high-frequency trading